Transcriptome Analysis Reveals AI-2 Relevant Genes of Multi-Drug Resistant Klebsiella pneumoniae in Response to Eugenol at Sub-MIC - Wang, Yi-ming; Dong, Wen-long; Odah, Kokou Ayefounin; Kong, Ling-cong; Ma, Hong-xia (Frontiers in Microbiology, 2019)
Eugenol, the major active essential oil component of clove, was reported possessing QS(quorum sensing) inhibitory activity. Previous study found that eugenol could bind to quorum sensing receptors of P.aeruginosa and down-regulate the expression of S.mutans virulence genes at sub-MIC(minimum inhibitory concentration) without affecting the bacterial growth. However, the alterations of QS signal molecules in K.pneumoniae at transcription levels was not well understood. To better understanding interactions of K.pneumoniae in response to eugenol and explore molecular regulations, transcriptome sequencing was performed. a total of 5779 differentially expressed genes (DEGs) enriched in a variety of biological processes and pathways were identified. The transcriptional data were validated by qPCR and the results showed that the expression profile of 4 major genes involved in autoinducers-2 (AI-2) synthesis, including luxS, pfs and lsrK were consistant with transcriptome analysis except for lsrR, a transcriptional repressor gene of lsr operon, which we speculate would repress the expression of following genes responsible for AI-2 signal transmission in vivo. In vitro AI-2 synthesis assay also revealed that eugenol could inhibit AI-2 generation. The results of our study offers insights into the mechanism of QS inhibitory activity and K.pneumoniae AI-2 alterations after treatment of eugenol.